Bad samaritan [videorecording (DVD)] - Tennant, David, 1971-; Sheehan, Robert, 1988-; Condon, Kerry, 1983- (Sony Pictures Home Entertainment, 2018)
A pair of burglars stumble upon a woman being held captive in a home they intended to rob.